Strategi Pengelolaan Limbah Padat Infeksius di Rumah Sakit Ibu dan Anak Family Jakarta Utara - Yulius Bria; Iman Basriman; Ninin Gusdini (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
The hospital is a health service that produces various infectious wastes that can endanger the officers who handle the waste and visitors and the community around the hospital. The purpose of the study was to determine the performance of infectious solid waste management at the Family Mother and Child Hospital, to determine the internal and external factors in the management of infectious solid waste at the Family Mother and Child Hospital, and to obtain the formulation of infectious solid waste management strategies at the Mother's Hospital. and Child Family. This research was conducted at the Mother and Child Family Hospital, North Jakarta, related to infectious solid waste management strategies. Data collection methods used are interviews, focus group discussions (FGD) and questionnaires. To get the main priority strategy using the IFE- EFE- IF- SWOT matrix. Research Results Based on the analysis of the QSPM matrix, there were 6 strategies that could be prioritized based on the highest ranking, namely (1) Implementing infectious solid waste management systems and procedures in a professional manner, (2) Improving the quality and competence of officers to prevent environmental pollution, (3) Conducting periodic socialization/training to employees related to infectious solid waste management, (4) Preparing medical waste management plans in accordance with the standards of the Minister of Health, (5) Providing sanctions to employees who do not follow the rules in handling infectious solid waste, (6) Optimizing the budget in infectious solid waste management.   Keywords: Infectious Solid Waste Management Strategy